The Design of a Revenue Dashboard for the Operational Division of PT XYZ Using the Kimball Four-Step Method - Arisandi, Debi; Siswanto, Teddy; Salim, Agus (Penerbitan Universitas Trisakti, 2025)
The rapid development of information technology drives the need for effective and efficient decision-making systems, particularly in the business world. This study aims to design a dashboard integrated with the operational division system of PT XYZ to address issues of slow decision-making processes. The dashboard is designed using the Online Analytical Processing (OLAP) for Step Kimball method, enabling multidimensional data analysis.The design process includes several stages: identifying requirements, designing a data warehouse based on the Kimball method, processing data using OLAP, and visualizing data with Tableau. The data utilized comprises critical information from the operational division, such as company profiles, contracts, collections, revenue, and credit scores. The results demonstrate that the designed dashboard effectively provides relevant information to support fast and accurate decision-making needs. The implementation of this dashboard is expected to improve operational efficiency and provide better strategic insights for PT XYZ.